Liolaemus duellmani Cei, 1978 (Reptilia: Squamata: Liolaemini), redescription of the holotype and variation in a microendemic and inadequately known species of Liolaemus from Northwestern Patagonia - Avila, Luciano Javier; Vrdoljak, Juan Esteban; Morando, Mariana (Zootaxa, 2021)
Liolaemus duellmani is a microendemic lizard described from southern Mendoza, Argentina, representing the southernmost distribution of the Liolaemus montanus species group. The original description was based on a small batch of preserved material and a juvenile collected alive. Along the years, this poorly known species was rarely collected or observed in the field, with no additional reports or findings published until a recent description of an adult female which was considered as a rediscovery of the species. Here, we redescribe the species and describe variation on external morphology, coloration, and some natural history observations.